Mobile Health untuk Pemantauan Kaki dalam Mencegah Ulkus Kaki Diabetik - Nurul Hendayani; Tuti Herawat; Prima Agustia Nova (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine the use of mobile health in preventing diabetic foot ulcers. The method used in this study is a literature review, where the electronic databases used are Pub Med and Clinical Key, published from 2015 to 2022. The keywords used are mobile health, diabetic foot care, and prevention of diabetic foot ulcers. The results show that mobile health technology helps people with diabetes carry out independent foot monitoring to prevent diabetic foot ulcers. Components of mobile health that can be used include monitoring foot temperature, foot descriptions, and directed guides for foot care. In conclusion, Mobile Health can help people with diabetes to prevent diabetic foot incidents. The Mobile Health application makes it easy for people living with diabetes to carry out foot monitoring. Keywords: Mobile Health, Diabetic Foot Care, Prevention of Diabetic Foot Ulcers